Variability of Seawater Chemistry in a Kelp Forest Environment Is Linked to in situ Transgenerational Effects in the Purple Sea Urchin, Strongylocentrotus purpuratus - Hoshijima, Umihiko; Hofmann, Gretchen E. (Frontiers in Marine Science, 2019)
While the value of giant kelp (Macrocystis pyrifera) as a habitat-forming foundation species is well-understood, it is unclear how they impact the oxygen concentration and pH of the surrounding seawater, and further, how such a dynamic abiotic environment will affect eco-evolutionary dynamics in a context of global change. Here, we profiled the nearshore kelp forest environment in Southern California to understand changes in dissolved oxygen (DO) and pH with high spatiotemporal resolution. We then examined transgenerational effects using sea urchins (Strongylocentrotus purpuratus) as our study organism. Using enclosures on the benthos, we conditioned adult sea urchins in situ at two locations - one inside the kelp forest and one outside the kelp forest. After a 11 week conditioning period timed to coincide with gametogenesis in the adults, the urchins were collected, spawned, and cultures of their progeny were raised in the laboratory in order to assess the performance of the progeny to simulated ocean acidification. In terms of the physical observations, we observed significant changes in DO and pH not only when comparing sites inside and outside of the kelp forest, but also between surface and benthic sensors at the same site. DO and pH at the benthos differed in mean, the amplitude of the diel signal, and in the profile of background noise of the signal. Ultimately, these results indicated that both DO and pH were more predictably variable inside of the kelp forest environment. On the biological side, we found that adult sea urchins inside the kelp forest produced more protein-rich eggs that developed into more pH-resilient embryos. Overall, this study in a temperate kelp forest ecosystem is one of the first studies to not only observe biological response to highly characterized environmental variability in situ, but also to observe such changes in a transgenerational context.